The Catholic Church in Taiwan Birth, Growth and Development (Christianity in Modern China, 2018)
This book provides a ground breaking interdisciplinary study of the Catholic Church in Taiwan, focusing on the post 1949 Civil War in China through to the present day, and discusses the role played by the Catholic Church in contemporary Taiwanese society. It considers the situation of the Catholic church of Taiwan during the Japanese Occupation, Taiwan-Vatican Relations from 1949 onwards and triangular Relations among the Vatican, Taiwan and China during Tsai Ing-wen's Administration. Written from a wide range of perspectives, from history and international relations to literature, philosophy, and education, this volume offers an important perspective on the birth and development of the Catholic Church in Taiwan, contributing a key work to religious studies in the Greater China Region.